Cold Atmospheric Plasma Ameliorates Skin Diseases Involving Reactive Oxygen/Nitrogen Species-Mediated Functions - Zhai, Si-yue; Kong, Michael G.; Xia, Yu-min (Frontiers in Immunology, 2022)
Skin diseases are mainly divided into infectious diseases, non-infectious inflammatory diseases, cancers, and wounds. The pathogenesis might include microbial infections, autoimmune responses, aberrant cellular proliferation or differentiation, and the overproduction of inflammatory factors. The traditional therapies for skin diseases, such as oral or topical drugs, have still been unsatisfactory, partly due to systematic side effects and reappearance. Cold atmospheric plasma (CAP), as an innovative and non-invasive therapeutic approach, has demonstrated its safe and effective functions in dermatology. With its generation of reactive oxygen species and reactive nitrogen species, CAP exhibits significant efficacies in inhibiting bacterial, viral, and fungal infections, facilitating wound healing, restraining the proliferation of cancers, and ameliorating psoriatic or vitiligous lesions. This review summarizes recent advances in CAP therapies for various skin diseases and implicates future strategies for increasing effectiveness or broadening clinical indications.